2014
DOI: 10.1002/lno.10012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated CO2 on the growth and toxicity of field populations and cultures of the saxitoxin-producing dinoflagellate, Alexandrium fundyense

Abstract: The effects of coastal acidification on the growth and toxicity of the saxitoxin-producing dinoflagellate Alexandrium fundyense were examined in culture and ecosystem studies. In culture experiments, Alexandrium strains isolated from Northport Bay NY, USA, and the Bay of Fundy, Canada, grew significantly faster (16 -190%; p<0.05) when exposed to elevated levels of pCO2 (~ 800- 1900μatm) compared to lower levels (~390μatm). Exposure to higher levels of pCO2 also resulted in significant increases (71 – 81%) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 78 publications
(193 reference statements)
1
32
0
Order By: Relevance
“…Kremp et al (2012) found an overall trend of increasing cell toxicity with increasing pCO 2 (and temperature) for eight strains of Alexandrium ostenfeldii . In culture experiments, strains of Alexandrium fundyense isolated from Northport Bay, New York, and the Bay of Fundy, Canada, grew significantly faster when exposed to elevated levels of pCO 2 compared to lower levels (Hattenrath-Lehmann et al, 2015), and high levels of pCO 2 significantly increased cellular toxicity in the Northport Bay strain but had no effect in the Bay of Fundy strain. In another study, acidification led to a doubling of saxitoxin concentrations in nutrient replete Alexandrium catenella , but toxicity increased by an order of magnitude under P limitation (Tatters et al, 2013a), indicating the OA effect was minor relative to nutrient status.…”
Section: Anticipated Linkages Between Harmful Algal Blooms and CLImentioning
confidence: 96%
“…Kremp et al (2012) found an overall trend of increasing cell toxicity with increasing pCO 2 (and temperature) for eight strains of Alexandrium ostenfeldii . In culture experiments, strains of Alexandrium fundyense isolated from Northport Bay, New York, and the Bay of Fundy, Canada, grew significantly faster when exposed to elevated levels of pCO 2 compared to lower levels (Hattenrath-Lehmann et al, 2015), and high levels of pCO 2 significantly increased cellular toxicity in the Northport Bay strain but had no effect in the Bay of Fundy strain. In another study, acidification led to a doubling of saxitoxin concentrations in nutrient replete Alexandrium catenella , but toxicity increased by an order of magnitude under P limitation (Tatters et al, 2013a), indicating the OA effect was minor relative to nutrient status.…”
Section: Anticipated Linkages Between Harmful Algal Blooms and CLImentioning
confidence: 96%
“…CO 2 -dependent changes have also been reported for other Alexandrium species. For instance, A. ostenfeldii showed increased STX under elevated pCO 2 (Kremp et al 2012), whereas A. catenella and A. fundyense (NPB8) displayed an increase in both STX and GTX1+ 4 under elevated pCO 2 (Tatters et al 2013, Hattenrath-Lehmann et al 2015. Thus, PSP toxin composition by Alexandrium species lacks an unambiguous response to elevated pCO 2 .…”
Section: Reallocation Of Energy From Ccm Down-regulationmentioning
confidence: 98%
“…PSP toxins are Nrich alkaloids with several analogues (Shimizu 1996, Cembella 1998, Anderson et al 2012b, and their synthesis has been shown to depend on N availability (e.g. Boyer et al 1987, Van de Waal et al 2013, 2014b, but also on changes in pCO 2 (Tatters et al 2013, Van de Waal et al 2014a, Hattenrath-Lehmann et al 2015. Little is yet known about the combined effects of N limitation and elevated pCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the negative effects of increased CO2 on calcifying organisms, previous studies have shown that some photosynthetic organisms, such as seagrasses (Koch et al, 2013;Palacios and Zimmerman, 2007), phytoplankton (Fu et al, 2012;Hattenrath-Lehmann et al, 2015), and macroalgae (Olischläger et al, 2013;Young and Gobler, 2016) may benefit from a high CO2 environment. Such photosynthetic autotrophs may also have the capacity to buffer carbonate chemistry, 15 potentially alleviating the harmful effects of excessive CO2 on calcifying organisms.…”
Section: Introduction 25mentioning
confidence: 87%